Elevating anthocyanin extraction from mangosteen pericarp: A comparative exploration of conventional and emerging non-thermal technology - Giroon Ijod; Nur Izzati Mohamed Nawawi; Rabiha Sulaiman; Mohammad Rashedi Ismail-Fitry; Noranizan Mohd Adzahan; Farooq Anwar; Ezzat Mohamad Azman (Food Chemistry: X)
Mangosteen pericarp (MP) is abundant in bioactive compounds but is often discarded as waste, leading to environmental pollution. This study compared the extraction of dried MP using maceration and high-pressure processing (HPP). HPP at 10 min (500 MPa/20 °C) resulted in the highest ACNs, total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activities. It also significantly reduced residual enzyme activities (REA) of polyphenol oxidase (PPO) and peroxidase (POD) by 33.90 % and 8.27 %, respectively. Fourier-transform infrared spectroscopy (FT-IR) analysis revealed a new wavelength at 2665.25 cm−1, and scanning electron microscopy (SEM) showed significant pore formation in MP cells, indicating cell damage. HPP-10 min enhanced the extraction of bioactive compounds, which significantly elevated the thermal stability of ACNs at 60 °C. This suggests that HPP is a promising method for extracting and preserving ACNs and other bioactive compounds from dried MP, with potential applications as natural colorants.